(3GdEHGfI aj JLhjO GdbQBfs - (3CHh GdCUHZ YHO GdYRjR Hf Ydj Hf eMeO Hf YHO GdYRjR Hf GdWMGf GdETHjdj, GHf GdWMGf,J (B560 (3g` s ((3HjJ GdebOS s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dG jfHZi GdMeO EdG dg MeOG jhGRi EfYGeg hEaVGdg hCTgO Cf dG Edg EdG Gddg hMOg dG TQjc dg s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: 3s
(3bQFJ Ydi NRYd Hf Ydi Hf Ndjd SfI (B595 (3g` HHjJ GdebOSs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B147s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs